Implementation of Hadith on Prayer Education for Children at Al-Biruni Mandiri Integrated Islamic Elementary School, Jipang, Rappocini District, Makassar City, South Sulawesi - Jumasni (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2023)
The main problem of this research is how to implement the Hadith of Prayer Education for Children at SIT Al -Biruni Mandiri, Kec.Rappocini, Makassar City, South Sulawesi?. The main problem is divided into several sub-problems: 1) What is the content of the hadith regarding prayer education for children? 2) What are the obstacles to the hadith regarding prayer education for children? 3) How to apply the hadith on prayer education to children at SIT Al -Biruni Mandiri, Kec.Rappocini, Makassar City, South Sulawesi. This research is classified as descriptive qualitative (qualitative field research) with a hadith and psychology approach. The data collection methods used are data sources (primary and secondary), observation, and interviews. Data analysis techniques were data reduction, presentation, and conclusions. The results of this study indicate that there are 13 hadith paths as a whole to pray for children. The researcher limits the nine books, namely seven narrations, through 2 companions and tabiin from 4 mukharrij. The quality of the hadith regarding the command to pray for children is considered valid because it meets the criteria for valid hadith, sanad, and matan. Based on research analysis of the results of interviews, educators who teach their students to pray have, based on what is in the hadith, to familiarize or provide lessons related to prayer to their students, especially grades one through three. In grade four, students are approaching ten years old, so students who break the rules will be punished, including memorizing short surahs and picking up trash. Through this thesis, it is hoped that parents and teachers will provide more intensive and continuous guidance and supervision to the children they are responsible. The presence of children in the school environment, which is only a few hours a day, only partially allows teachers to provide valuable education, including religious education. Therefore, an educational collaboration between parents and schools is needed so that children are expected to be serious about applying it to everyday life.